(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Spirituality, a scan for extraordinary significance or the faith in some kind of more prominent presence outside of mankind, can be connected to religion, however the act of spirituality is by and large considered to go past religion and connection people with something bigger, for example, the universe itself. This paper is an investigation on effectiveness of religious coping mechanism in the process of counselling in psychology.